PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN UMKM KONVEKSI SETIA KAWAN - Ismartaya, Ismartaya; Silaningsih, Endang; Frawitazian, Nadilla (Journal of Management Small and Medium Enterprises (SMEs), 2024)
The purpose of this study is to ascertain how Konveksi Setia Kawan MSME employees' performance is impacted by organizational culture, work environment, and work motivation. Organizational culture, work environment, and work motivation were the independent variables employed in this study, and 46 individuals were sampled. Meanwhile, the dependent variable used in this research is employee performance. The research data was collected using questionnaires. The analytical method used is the multiple linear regression method. The results of this research show that 1) organizational culture has a positive and significant effect on employee performance; 2) the work environment has a positive and significant effect on employee performance; 3) work motivation has a positive and significant effect on employee performance; 4) organizational culture, work environment, and work motivation have a positive and significant effect on the performance of Konveksi Setia Kawan MSME employees. Keywords: Organizational Culture; Work Environment; Work Motivation; Employee Performance